USED MINING PIT (VOID) LIMESTONE MINE IN PT. SEMEN BATURAJA (PERSERO) TBK FOR FRESHWATER AQUACULTURE PONDS. - Mgs. M. Fahmi Ramadhan; Restu Juniah; Hartini Iskandar (Indonesian Journal of Environmental Management and Sustainability, 2018)
In meeting the needs of cement raw materials of limestone, PT Semen Baturaja (Persero) Tbk do its own mining activities. Mining activities will have an impact on the surrounding environment. Positive impacts arising from mining activities such as increasing the income of the surrounding community, opening jobs, and so forth. Meanwhile, the negative impacts caused are the change in the natural order and the color of the earth, noise, air pollution, water quality degradation, and others. Changes in the natural order that will be generated after mining activities are completed, one of which is a mine hole (void). The climate in South Sumatra, this region is generally included in tropical regions. The geology of the Baturaja formation is generally included in the Palembang group, which has Tma, Qtk and Tmpm formations. Mining activities at the limestone quarry of PT. Semen Baturaja (Persero) Tbk., carried out in two ways, it was surface mining, and blasting activity. Freshwater fish aquaculture will be carried out to provide economic value and can be used as an indicator that the water contained in voids is not dangerous, and it’s still in a standard regulated by the government.